Tingkat Stres Pada Mahasiswa dalam Pelaksanaan Praktik Profesi Ners Stase Keperawatan Medikal Bedah - Dewi Wijayanti; Najihah Najihah; Ferly Yacoline Pailungan (Universitas Pahlawan Tuanku Tambusai, 2026)
Students are vulnerable to stress caused by the transition from college to hospital practice. The purpose of this study was to determine the stress levels of nursing students practicing in the medical-surgical nursing program. A sample of 50 respondents was selected using a purposive sampling technique. Data collection used the DASS-42 (Depression Anxiety Stress Scale 42) questionnaire. Univariate analysis was used using descriptive statistical tests. The results showed that physical stress was highest at a moderate level (32 students), emotional stress was highest at a moderate level (31 students (62%), cognitive stress was highest at a moderate level (31 students (62%), and behavioral stress was highest at a moderate level (33 students (66%). The recommendations for future researchers include: The results of this study can serve as a reference and allow them to continue researching the factors influencing stress levels in students across all programs.